Effect of deposition temperature on the structural and optical properties of chemically prepared nanocrystalline lead selenide thin films - Begum, Anayara; Hussain, Amir; Rahman, Atowar (Beilstein Journal of Nanotechnology, 2012)
Nanocrystalline lead selenide (PbSe) thin films were prepared on glass substrates by a chemical bath deposition method, using sodium selenosulfate (Na2SeSO3) as a source of Se2− ions, and lead acetate as a source of Pb2+ ions. Trisodium citrate (TSC) was used as a complexing agent. PbSe films were prepared at various deposition temperatures while the pH value was kept fixed at 11, and the effect on the resulting film properties was studied by X-ray diffraction (XRD), X-ray fluorescence (XRF), scanning electron microscopy (SEM) and optical absorption studies. The structural parameters, such as the lattice constant (a), crystallite size (D), dislocation density (ρ) and microstrain (ε) were evaluated from the XRD spectra. It was found that average crystallite size, as calculated from Scherrer’s formula, increased from 23 to 33 nm as the deposition temperature was varied from 303 to 343 K. The dislocation density and microstrain were found to vary inversely with the crystallite size, whereas the lattice constant was found to increase with an increase in crystallite size. The optical absorption spectra of the nanocrystalline PbSe films showed a blue shift, and the optical band gap (Eg) was found to increase from 1.96 to 2.10 eV with the decrease in crystallite size.
Keywords: chemical bath deposition; lattice parameter; lead selenide; Nelson–Riley plot; optical absorption